The moderation effects of task attributes and mental fatigue on post-interruption task performance in a concurrent multitasking environment. (July 2022) - Chen, Yueyuan; Fang, Weining; Guo, Beiyuan; Bao, Haifeng
Abstract: In a concurrent multitasking environment, performing many types of tasks increases task complexity, and working long hours makes a person susceptible to mental fatigue. Emerging technologies may lead to more task interruptions. This study examines the effects of task attributes and mental fatigue on interrupted task performance in a concurrent multitasking environment. Thirty-four participants performed the MATB-Ⅱ under eight conditions (two-level task interruption, two-level task complexity, two-level fatigue). The results revealed the significant interaction effects of interruption × task complexity and of interruption × fatigue state. The findings show that more time is required to return to a complex primary task, and there are differences among subtask types. Mental fatigue negatively affects primary task performance, workload, and the resumption lag after an interruption. The findings are explained by the increasing information cues needed to resume complex tasks and the negative effect of fatigue on memory activation. Highlights: Investigated the impact of mental fatigue and task complexity on interruption. Mental fatigue and high complexity tasks aggravate the negative effects of task interruption. Different types of subtasks in concurrent multitasking are affected differently by interruptions. Provided a theoretical basis to optimize interruption in concurrent multitasking environments.